LEARNING, DOING AND PROFESSIONAL DEVELOPMENT – THE RIVER STYLES FRAMEWORK AS A TOOL TO SUPPORT THE DEVELOPMENT OF COHERENT AND STRATEGIC APPROACHES FOR LAND AND WATER MANAGEMENT IN BRAZIL - Fryirs, Kirstie; Brierley, Gary; Marçal, Mônica dos Santos; Peixoto, Maria Naíse; Lima, Raphael (Revista Brasileira de Geomorfologia, 2019)
Ongoing development, training and adaptive learning are fundamental to professional practice in river science and management. River Styles Framework provides a coherent, carefully structured (scaffolded) approach that synthesises geomorphic understandings of rivers as a baseline to support river management applications. As the approach is generic, principles and procedures can applied in any setting. The Framework and its applications build on fundamental research into river forms and processes. Importantly, the Framework was developed in collaboration with river management agencies in New South Wales, Australia and has been used in collaboration with practitioners elsewhere in the world. This paper documents the process used to teach the five-day River Styles professional short course in Brazil, September 2017. We report upon some pedagogical foundations of the Framework to explain the approach to teaching. We present an overview of the types of exercises taught in Brazil, showing how local fieldwork and case studies support the uptake of this geomorphic information to inform river management. We emphasise the importance of careful planning in delivering a coherent product that integrates remotely-sensed work, field interpretation skills and lecture/practical class exercises. These exercises build upon foundation research in fluvial geomorphology in the Macaé Catchment in Rio de Janeiro State.